Misi dalam Dunia Kerja, Memahami Peran dan Pelaksanaanya - Sitompul, Baginda; Lumbantobing, Sandro M; Simanungkalit, Relina M; Sinaga, Junita D; Sihombing, Talup (LANCAH: Jurnal Inovasi dan Tren, 2024)
This research is intended to provide correct understanding and implementation regarding the meaning of work as a mission for Christians. The method used is literature research. The results of this research are that work as a mission is very important even for Christian leaders as a means of proclaiming God's shalom to the world. In this way, the Missio Dei which is mandated to the church by God becomes real and effective to be carried out in various aspects of life, especially in the field of work carried out by Christians. There are at least five implications for Christians. First, understand the strategic calling of every believer who is called as a church leader. Second, understanding the meaning of God working for and through His people as believers. Third, understand the meaning of vocation for every Christian who believes in Christ Jesus. Fourth, be a Christian who works ethically. Fifth, understand the principle of work as a calling to mission.